New opportunities for weed control in maize - Sharma, A. R.; Suryabanshi, Tarun; Das, T. K. (Indian Farming, 2019)
The use of herbicides in the present context appears to be indispensable but these chemicals need to be applied judiciously for effective weed control that through herbicides requires technical expertise and experience. The following precautions must be observed: • It is essential to ensure adequate soil moisture at the application of preemergence herbicide like atrazine and pendimethalin. • Directed spray of paraquat should be undertaken by using a hood with utmost care when the maize plants have reached about 1 m height and the inter-row weeds are trampled to the ground level. • Ensure at least 3-4 hours of bright sunshine after the application of post-emergence herbicide so that it is absorbed and translocated into the weed plant system. • Atrazine can also be applied as tank–mix along with tembotrione or topramezone as early postemergence (15-20 days after sowing) in case there is no serious problem of early infestation of weeds. • Pre-sowing application of nonselective herbicides like paraquat and glyphosate is essential in case there are previously growing weeds in the field at sowing of zero-till maize. • Never apply 2,4-D when maize was intercropped with any other broadleaved crop like legume, oilseed or vegetable. Such crops grown in the vicinity of maize may also be affected by the spray drift of 2,4-D. • Do not apply 2,4-D as postemergence when the maize is largely infested with grassy weeds.